A qualitative analysis of STEM female’s coping strategy under the COVID-19 pandemic - Tien, Hsiu-Lan Shelley; Gong, Lei; Wang, Wei-Hsuan; Lee, James (Frontiers in Public Health, 2023)
Mental health is an important issue after the pandemic. The purpose of the research was to realize the STEM female's career coping under the pendemic. We conducted in-depth interviews with three STEM female engineers in Silicon Valley, California. How they copy with the conflicts between work and family under the covid pressure? Our qualitative interviews found that the resilience created under the covid-19 pressure enabled those female engineers take care of family members while they worked at home. The new working model fits them quite well. The coworker interactions can still kept through the computers. Generally speaking, they are quite satisfied with the new normal working model. More mental health issues are discussed in the manuscript.